Penguatan Pendidikan Karakter (PPK) Berbasis Profil Pamong Belajar Pada Kejar Paket C di SKB Gresik - Arum, Dewi Wulan; Siswanto, Heru (J+PLUS UNESA, 2024)
If pamong belajar has the competence and potential to insert character education, it will indirectly shape the quality of character in accordance with the objectives of Strengthening Character Education (PPK). Character education is strengthened by providing understanding and emphasizing students on the five main values of PPK, namely: (a) religious character values, (b) independent character values, (c) nationalism character values, (d) mutual cooperation character values, and (e) integrity character values. This research focuses on: (1) the implementation of PPK, (2) the profile of learning assistants in the implementation of PPK. This research used a qualitative approach with a descriptive approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation. The results showed that: (1) the implementation of the five main values of PPK in Study Group of Packages C students that is most prominent and easy to do through various activities is the value of religious character, although not all five values can be implemented, and (2) the involvement of learning assistants based on their educator profiles through planning, implementation, and assessment has not been maximized.